2018
DOI: 10.1155/2018/4237354
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Diabetes Mellitus-Induced Male Rat Reproductive Dysfunction with Micro-NanoencapsulatedEchinacea purpureaEthanol Extract

Abstract: Diabetes mellitus is a major health problem that affects a patient's life quality throughout the world due to its worst complications. It was recognized that chronic hyperglycemia with oxidative stress was the major cause of male infertility. Echinacea purpurea ethanol extract (EE) contains phenolic acid and isobutylamides had been proven to ameliorate diabetic complications. Chitosan/silica nanoparticles are well-known in the medicinal field because of its controlled release and drug delivery properties. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Additionally, some studies examined the models with hyperglycemia or insulin resistance. Echinacea purpurea ethanol extract, Lycium barbarum polysaccharide, and white tea showed restoration of reproductive function as well as blood glucose levels against STZ-induced diabetic mice [ 63 , 84 , 88 ]. To add, apoptotic activities by the administration of natural products were observed through the regulation of indicators such as c-caspase3, 8, and bcl-2 [ 43 , 54 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some studies examined the models with hyperglycemia or insulin resistance. Echinacea purpurea ethanol extract, Lycium barbarum polysaccharide, and white tea showed restoration of reproductive function as well as blood glucose levels against STZ-induced diabetic mice [ 63 , 84 , 88 ]. To add, apoptotic activities by the administration of natural products were observed through the regulation of indicators such as c-caspase3, 8, and bcl-2 [ 43 , 54 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Echinacea purpurea Linn. also known as purple coneflower contains active compounds with antioxidative, anti-inflammatory, antibacterial, antiviral, and anticancer properties [ 88 ]. Mao et al reported that Echinacea purpurea ethanol extract encapsulated with chitosan/silica nanoparticles (nano-EE) ameliorated diabetes related male infertility.…”
Section: Plant Extract and Infertilitymentioning
confidence: 99%
“…China as this rat model is the classic model for studying DM. 25,26 After the adaption for 4 weeks, streptozotocin (STZ,60 mg/kg; Sigma-Aldrich) was dissolved in the vehicle (0.1 mol/L citratephosphate buffer; pH = 4.2) and injected into 25 rats to induce type 1 DM. The same vehicle was injected into the other 20 rats.…”
Section: Berberine (Bb) the Major Active Component Isolated Frommentioning
confidence: 99%
“…Both Echinacea angustifolia and Echinacea purpurea were shown to improve symptoms of colitis in rats by decreasing the number of inflammatory mediators (IL-1β and TNF-α) [84]. Echinacea preparations were also reported to reduce inflammatory conditions caused by insulin resistance and induced by pathogens, respectively [79,85,86,87,88,89].…”
Section: General Function Of Fructans In the Human Bodymentioning
confidence: 99%